European Code against Cancer 4th Edition: Alcohol drinking and cancer. (December 2015) - Scoccianti, Chiara; Cecchini, Michele; Anderson, Annie S.; Berrino, Franco; Boutron-Ruault, Marie-Christine; Espina, Carolina; Key, Timothy J.; Leitzmann, Michael; Norat, Teresa; Powers, Hilary; Wiseman, Martin; Romieu, Isabelle
Abstract: Alcohol consumption is the third leading risk factor for disease and mortality in Europe. The International Agency for Research on Cancer (IARC) Monographs provide strengthened evidence that the consumption of alcoholic beverages is causally associated with cancers of the oral cavity, pharynx, larynx, oesophagus, liver, colorectum and female breast, even for low and moderate alcohol intakes. The risk of cancer increases in a dose-dependent manner, and the higher the amount of alcohol consumed, the higher the risk of developing cancer. Several biological mechanisms explain the carcinogenicity of alcohol; among them, ethanol and its genotoxic metabolite acetaldehyde play a major role. Taking all this evidence into account, a recommendation of the 4th edition of the European Code against Cancer (ECAC) is: "If you drink alcohol of any type, limit your intake. Not drinking alcohol is better for cancer prevention."